2017
DOI: 10.1097/olq.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Use of Patient-Delivered Partner Therapy in US College Settings: Associations With Legality, Perceived Legality and Other Sexual and Reproductive Health Services

Abstract: PDPT was more likely to be available in colleges that offered SRH services and where staff believed PDPT was legal. Further research could explore more precise conditions under which PDPT is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Many respondents were uncertain about EPT legality in their state. Expedited partner therapy provision was associated with perceived legality; EPT was more likely to be offered if the respondent believed it was legal 12 . However, unlike the prior CHC EPT study, 13 actual legality was not related to EPT provision 12 …”
Section: Ept Provision On College Campusesmentioning
confidence: 90%
See 4 more Smart Citations
“…Many respondents were uncertain about EPT legality in their state. Expedited partner therapy provision was associated with perceived legality; EPT was more likely to be offered if the respondent believed it was legal 12 . However, unlike the prior CHC EPT study, 13 actual legality was not related to EPT provision 12 …”
Section: Ept Provision On College Campusesmentioning
confidence: 90%
“…Expedited partner therapy provision was associated with perceived legality; EPT was more likely to be offered if the respondent believed it was legal. 12 However, unlike the prior CHC EPT study, 13 actual legality was not related to EPT provision. 12 All 3 studies concluded that there are missed opportunities for STI prevention at CHCs given low rates of EPT provision and recommended more research on EPT at CHCs be conducted.…”
Section: Ept Provision On College Campusesmentioning
confidence: 93%
See 3 more Smart Citations